PENGEMBANGAN SARANA DAN PRASARANA MICE JAWA TIMUR PARK GROUP - Agustinus Doedyk Setiyawan; Aminudin Azis; Endhita Kumalasari (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2021)
Facilities and infrastructure is one of the main things in the company. Facilities and infrastructure are sometimes identical to the facilities that have been provided or will be provided. Especially in private companies such as Jawa Timur Park Group, which is engaged in providing Meeting Incentive Convention Exhibition (MICE) services. The development of MICE infrastructure aims to improve the quality of the company in accordance with the plan. The purpose of this study was to determine the extent of the development of MICE Facilities and Infrastructure in Jawa Timur Park Group, especially Jawa Timur Park 3. The method used was descriptive qualitative with primary and secondary data sources, the data were obtained through interviews, observation, and documentation. The validity of the data was tested by triangulation of techniques and sources. The results obtained indicate that the development of MICE facilities and infrastructure in East Java Park 3 Batu includes (1) basic facilities, (2) complementary facilities, (3) supporting facilities, (4) economic infrastructure, (5) social infrastructure, and (6 ) tourism infrastructure. The development of facilities and infrastructure to support MICE activities is carried out by considering the needs and convenience of visitors and minimizing the impact of the Covid-19 pandemic, through health protocol facilities. The development of facilities and infrastructure will continue to be carried out considering that there is still a lot of potential that East Java Park 3 Batu has.